INVESTMENT INTEREST AMONG GENERATION Z - Rahma Winda, Silvi; PURWIDIANTI, WIDA; Bagis, Fatmah; Nazah, Nawalin (Universitas Muhammadiyah Pontianak, 2026)
Generation Z’s investment interest has become an important issue as young people increasingly participate in the investment market. This study examines the effects of financial literacy, investment motivation, minimum capital, and technological advancement on the investment interest of Generation Z in Java. Using a quantitative approach, data were collected from 210 respondents through purposive sampling and analyzed using SEM-PLS 4. The findings reveal that minimum capital and technological advancement significantly influence investment interest, whereas financial literacy and investment motivation do not. These results suggest that affordable capital requirements and technological accessibility are the main drivers of Generation Z’s investment interest. Keywords: Financial Literacy; Investment Motivation; Minimum Capital; Technological Progress; Investment Interest